Challenges to neurology residency education in today's health care environment. Issue 3 (4th August 2016) - Bega, Danny; Krainc, Dimitri
Abstract : Residency training has had to adapt to higher patient volumes, increased complexity of medical care, and the commercialized system of health care. These changes have led to a concerning culture shift in neurology. We review the relationship between the emerging health care delivery system and residency training, highlighting issues related to duty hours and work‐life balance, the changing technological landscape, high patient volumes, and complex service obligations. We propose that the current challenges in health care delivery offer the opportunity to improve neurology residency through faculty development programs, bringing teaching back to the bedside, increasing resident autonomy, utilizing near‐peer teaching, and rewarding educators who facilitate an environment of inquiry and scholarship, with the ultimate goal of better alignment between education and patient care. Ann Neurol 2016;80:315–320